Experience of Online Learning at Nursing Students - Lilik Setiawan; Nurul Laili (STIKep PPNI Jawa Barat, 2021)
Background: Online learning uses the capabilities of learning access, connection, flexibility, and interaction.Nursing students experience many changes in learning models, one of which is a laboratory and clinical practice activities. Purpose: This study focuses on student experiences, especially knowing the perceptions, expectations, and things that can support and hinder the online learning process. Methods: Qualitative research through a descriptive phenomenology approach to nine participants using the purposive sampling technique.The data were collected by interview and analyzed using the Colaizzi method. Result: This qualitative research resulted in 7 themes covering perceptions of the use and change of supporting facilities, financial perceptions of online learning, psychological perceptions of online learning, innovation and creativity in thinking, accessibility to learning, family support and learning motivation. Thematic analysis is obtained from theme 1 has 2 categories and 3 codings, theme 2 has 2 categories and 3 codings, theme 3 has 3 categories and 7 codings, theme 4 has 1 categories and 2 codings, theme 5 has 2 categories and 2 codings, theme 6 has 2 categories and 4 coding, theme 7 has 1 categories and 2 coding. The online learning experience during the Covid-19 pandemic for students provides an overview of alternatives that can be used as references for lecturers in assessing and evaluating learning outcomes, perceptions, expectations, and things that can support and hinder students in online learning. Conclusion: The results of the research as an evaluation material for lecturers so that learning can be carried out effectively. The data obtained from the research results can be used as input in scientific development about online learning experiences and can be used as competency parameters that must be possessed by nurses.